Putting a price on carbon : from Lima to Paris 2015 - Goh, Tian (2014)
The 20th session of the UNFCCC Conference of Parties in Lima now underway until 12 December 2014 will discuss how to put a price on carbon. The question is how can a carbon price bring us closer to our emission targets?